Formation and Ripening of Nanobelts/Nanofibers under Stirring of aqueous Solution – alternative models - Korol, Yaroslav; Gusak, Andriy; Danielewski, Marek; Gajewska, Marta (Diffusion Fundamentals, 2022)
Problem of V2O5 nanobelts production under intensive stirring of V2O5 powder in salted water is revisited. Method was initially proposed in 2016 but models and understanding were lacking. Here an independent attempt of the controlled V2O5 nanobelts formation and growth under stirring with various rotation frequencies is reported, as well as some alternative mechanisms and respective mathematical models of the nanobelts growth and ripening kinetics.